Gambaran Pengelolaan Obat Kadaluwarsa Di Puskesmas Wilayah Kabupaten Pemalang - Dita Evelina Azzahra; Musa Fitri Fatkhiya (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
The management of expired medications in community health centers (Puskesmas) is crucial because it directly relates to the quality of healthcare services, patient safety, and environmental impact. Medications that have passed their expiration date no longer guarantee effectiveness and safety, and therefore require proper handling in accordance with applicable regulations. Furthermore, improper management can lead to waste and the risk of misuse. This study was conducted to describe the expired medication management system in community health centers (Puskesmas) in Pemalang Regency, specifically regarding separation, recording, reporting, and destruction. This study used a descriptive method with a cross-sectional approach to describe the conditions in the field. The data used were primary data obtained through direct observation and interviews with pharmacists at the community health centers. Sampling was conducted using purposive sampling at five community health centers: Losari, Purwoharjo, Sarwodadi, Rowosari, and Kebandaran. The instrument used was an observation sheet as an interview guide, while the collected data was analyzed descriptively to provide an overview of the implementation of expired medication management. The study results indicate that all community health centers (Puskesmas) have properly separated, recorded, and reported expired medications in accordance with regulations. Overall, the management of expired drugs in health centers in the Pemalang Regency area has been running well and in accordance with the guidelines of the Indonesian Food and Drug Supervisory Agency (BPOM) Regulation Number 20 of 2025 concerning Good Distribution Practices for Medicines (CDOB), reaching 100%.